The role of serotonin in the control of mood anf appetite in humans - Oldman, A; Oldman, Anna Dorothy (1994)
This thesis addresses the effects of pharmacological manipulations of brain 5- hydroxytryptamine (5-HT, serotonin) and it's precursor, tryptophan, on appetite and mood in humans. Chapter 1 is a presentation of the literature reviewed in order to carry out the studies contained within this thesis. General methods are described in Chapter 2; these include biochemical methods for analysis of plasma tryptophan, and measures and assessment methodologies for analysis of appetite and mood. This chapter also contains a pilot study of the methodology adopted for lowering plasma tryptophan levels. The first experiment (Chapter 3) examines the effects of calorie controlled dieting on plasma tryptophan, mood and appetite using a longitudinal design. Dieters were compared with a matched control group, and the results demonstrated that whilst dieting does not appear to alter mood or responses to food in a laboratory setting, it does lower levels of plasma tryptophan compared with baseline and with controls. In view of the confounding variables of dieting on mood and appetite, the second experiment (Chapter 4) examined the effects of an acute, laboratory based depletion of plasma tryptophan on these parameters in healthy female volunteers acting as their own controls. Significant depletion of plasma tryptophan was not associated with alterations in mood or appetite. The third experiment (Chapter 5) addresses the issue of predisposing factors in the effects of tryptophan depletion on mood and appetite. This was carried out with a group of women who had recovered from an eating disorder (bulimia nervosa). These subjects were acting as their own controls but were also compared directly with the non-clinical group of subjects from the previous experiment. This experiment demonstrated interesting differences in the eating behaviour of the two groups, and a significant difference in baseline levels of total plasma tryptophan. There were, however, no effects of tryptophan depletion on mood or appetite in the women who had recovered from bulimia nervosa. In view of the apparent lack of effect of tryptophan depletion on mood or appetite, the remaining two experiments examine the role of specific 5-HT receptor subtypes in the control of appetite. Chapter 6 examines the effect of meta-chlorophenylpiperazine (mCPP), a 5-HT2C receptor agonist on appetite, and Chapter 7 examines the effect of 5-HT3 receptor blockade on amphetamine anorexia. Whilst the data from these experiments do not support a role for these receptor subtypes in appetite, it is suggested that this is a potentially fruitful area for future research. The results generated by the above experiments are discussed in Chapter 8 in the light of other research findings. The methodologies adopted for these experiments and the implications of these studies for future research are discussed.